The analysis of design metrics on open source systems - Awang Abu Bakar, Normi Sham (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The recent development in software measurement looks at many aspects of software projects, from requirements gathering, analysis, design, coding and testing. The main focus of this paper is to investigate the correlation between post-delivery defects of a selection of open source systems with several design metrics based on the Card and Glass model. This model is comprised of Structural Complexity which is represented by Coupling between Object (CBO), Data Complexity is represented by number of parameters and System Complexity is the combination of Structural and Data Complexity. The results show that only Structural Complexity has correlation with defects. The contribution of this paper is the implementation of structured metrics to object-oriented systems.